Clinicopathological features of cytokeratin 5‐positive pulmonary adenocarcinoma. Issue 3 (7th November 2022) - Terada, K; Yoshizawa, A; Sumiyoshi, S; Rokutan‐Kurata, M; Nakajima, N; Hamaji, M; Sonobe, M; Menju, T; Date, H; Haga, H
Abstract : Cytokeratin 5 (CK5) is a marker for pulmonary squamous cell carcinoma; however, CK5 is sometimes present in pulmonary adenocarcinoma (ADC), and there is insufficient information regarding the clinicopathological features of CK5‐positive ADC. We aimed to explore the clinicopathological characteristics of CK5‐positive ADC using immunohistochemistry. We prepared the following two cohorts: a resected cohort containing 220 resected tumours for primarily studying the detailed morphological characteristics, and a tissue microarray (TMA) cohort containing 337 samples for investigating the associations of CK5 expression with other protein expressions, genetic and prognostic findings. CK5‐positive ADC was defined to have ≥ 10% tumour cells and presence of CK5‐positive tumour cells in the resected and TMA cohorts, respectively. CK5‐positive ADCs were identified in 91 (16.3%) patients in the combined cohort. CK5‐positive ADCs had male predominance ( P = 0.012), smoking history ( P = 0.001), higher stage ( P < 0.001), histological high‐grade components ( P < 0.001), vascular invasion ( P < 0.001), mucinous differentiation ( P < 0.001), spread through airspaces ( P < 0.001), EGFR wild‐type ( P < 0.001), KRAS mutations ( P < 0.001), ALK rearrangement ( P < 0.001) and ROS1 rearrangement ( P = 0.002). In the resected cohort, more than half the CK5‐positive ADCs (19 cases, 65.5%) showed mucinous differentiation; the remaining cases harboured high‐grade components. In the TMA cohort, CK5‐positive ADCs correlated with TTF‐1 negativity ( P = 0.002) and MUC5B, MUC5AC and HNF4alpha positivity ( P < 0.001, 0.048, < 0.001). Further, CK5‐positive ADCs had significantly lower disease‐free and overall survival rates than CK5‐negative ADCs ( P < 0.001 for each). Additionally, multivariate analysis revealed that CK5 expression was an independent poor prognostic factor. CK5‐positive ADCs showed aggressive clinical behaviour, with high‐grade morphology and mucinous differentiation. Abstract : XXX